Increase in scabies incidence: a retrospective cohort study - Bener, Fidan (The European Research Journal, 2021)
Objectives: Recently, there are studies from many countries reporting that scabies incidence has increased. Similarly, there was an increase in the frequency of scabies admitted to our outpatient clinic. Our aim in this study is to draw attention to the increasing incidence of scabies in our region. Methods: The cases diagnosed with scabies in dermatology outpatient clinic between 2010-2019, their demographics and treatments were retrospectively analyzed. Results: It was detected that 949 (0.55%) scabies cases were diagnosed between 2010-2019. When it was analyzed by years, the 3.5 times increase in cases with scabies in 2014 compared to the previous year was found statistically significant (p < 0.05). When data from 2018 was compared with the data from 2010, an increase in the number of cases by 7.6 times was detected in the outpatient numbers with scabies and by 4.7/1000 person-years times in the general population (p < 0.05). Besides, it was determined that the Syrian asylum seekers started to apply to our outpatient clinic as of 2014, and that the scabies incidence was very high within the same year in these patients (27.6%). It was detected that permethrin was prescribed by 88.4% to 868 cases whose treatment details were achieved, and that the ratio of response to treatment was 95.8%. Conclusion: The results we obtained reveal that there was an increased scabies incidence from 2014 in our region. The necessity to immediately and effectively intervene the affected cases to prevent possible epidemic attacks has formed.